Materials Encyclopedia for Creatives. - Ternaux, Elodie, ....- (Basel : Birkhäuser, 2022)
Materials and the myriad technologies that have been developed to manipulate them are of essential relevance to product designers, architects, artists and stylists, as they represent the starting point for every product and every architectural work. The book is an encyclopaedic compendium of around 1,000 terms in this field, from aerogel to marble to zirconium. It features traditional and frequently used materials, as well as new and unexpected ones. Their respective advantages and disadvantages are precisely described. In addition, terms related to production processes, such as upcycling or tanning, or that describe the properties of materials or are closely related to the topic have also been included.
Keywords: Design; Materiaalkunde; Materialen; Productdesign